Methods for characterization and evaluation of chemoresistive nanosensors - Felix, Anderson A. [UNESP]; Suman, Pedro H. [UNESP]; Orlandi, Marcelo O. [UNESP] (Elsevier, 2020)
Chemoresistive gas sensors based on nanomaterials have been an emerging technology to monitor pollutant gases in the environment. This chapter is devoted to report the relevant scientific and technological developments made on the characterization and evaluation of these kinds of sensors. Fundamental parameters to assess the performance of semiconducting metal oxides as gas sensors are discussed as well as the recent advances on the configuration of nanosensor-based devices. The main characterization methods applied to analyze the features of nanostructured sensing layers based on semiconducting metal oxide materials have also been presented as well as their contribution toward elucidating its gas sensing properties. The operation principles of in situ and operando characterization approaches and their contribution to the understanding of surface reactions responsible for gas-sensing effects are also described.
Keywords: characterization techniques; Chemoresistive gas sensors; in situ and operando methods; nanomaterials; sensing layer; SMOx materials